THE INFLUENCE OF DISTRIBUTIVE JUSTICE COMPENSATION AND TRANSFORMATIONAL LEADERSHIP STYLE ON AFFECTIVE COMMITMENT EMPLOYEES - Muhammad Maulana Darmawan (JCOMENT (Journal of Community Empowerment), 2021)
The purpose of this study was to analyze the effect of compensation distributive justice and transformational leadership on the affective commitment of employees of PT. Rizky Artha Mulia Bersujud, South Borneo. The subjects in this study were employees of PT. Rizky Artha Mulia Bersujud with a minimum of 1 year work for the company. This research was conducted with a total of 115 respondents who had been determined using non-probability sampling techniques and distributed questionnaires to respondents using offline questionnaires. The analytical tool used by the author is the multiple regression analysis techniques with SPSS 16 as the application program. Based on the results of the study, it shows that compensation distributive justice and transformational leadership have a significant positive effect on affective commitment.